B Corp versus ISO 9001 and 14001 certifications: Aligned, or alternative paths, towards sustainable development? - Fonseca, Luís (2021)
Corporate social responsibility (CSR) emerged to deliver sustainable economic, environmental, and social value to organization's extended stakeholders and society in general. This study investigates the similarities, differences, and relationships between B Corp, ISO 9001, and ISO 14001 certifications and is supported by a mixed research methodology and a sample of 701 B Corp companies certified between January 2020 and March 2021. The results indicate that ISO 14001 and ISO 9001 certified B Corp companies have statistically higher scores for the Environment dimension but are inconclusive, or even contradictory, for the other BIA (B Impact Assessment) dimensions. Differences in size, activity sector and geographical location are discussed. It is shown that both B Corp, ISO 9001 and 14001 certified companies, guided by different missions and business models, contribute, at different levels, towards CSR and sustainable development goals.